Mitochondrial AIF loss causes metabolic reprogramming, caspase-independent cell death blockade, embryonic lethality, and perinatal hydrocephalus - Laure Delavallée; Navrita Mathiah; Lauriane Cabon; Aurélien Mazeraud; Marie-Noelle Br; Leticia K. Lerner; Mariana Tannoury; Alexandre Prola; Raquel Moreno-Loshuertos; Mathieu Baritaud; Laura Vela; Kevin Garbin; et al. (Elsevier, 2020)
Objectives: Apoptosis-Inducing Factor (AIF) is a protein involved in mitochondrial electron transport chain assembly/stability and programmed cell death. The relevant role of this protein is underlined because mutations altering mitochondrial AIF properties result in acute pediatric mitochondriopathies and tumor metastasis. By generating an original AIF-deficient mouse strain, this study attempted to analyze, in a single paradigm, the cellular and developmental metabolic consequences of AIF loss and the subsequent oxidative phosphorylation (OXPHOS) dysfunction. Methods: We developed a novel AIF-deficient mouse strain and assessed, using molecular and cell biology approaches, the cellular, embryonic, and adult mice phenotypic alterations. Additionally, we conducted ex vivo assays with primary and immortalized AIF knockout mouse embryonic fibroblasts (MEFs) to establish the cell death characteristics and the metabolic adaptive responses provoked by the mitochondrial electron transport chain (ETC) breakdown. Results: AIF deficiency destabilized mitochondrial ETC and provoked supercomplex disorganization, mitochondrial transmembrane potential loss, and high generation of mitochondrial reactive oxygen species (ROS). AIF-/Y MEFs counterbalanced these OXPHOS alterations by mitochondrial network reorganization and a metabolic reprogramming toward anaerobic glycolysis illustrated by the AMPK phosphorylation at Thr172, the overexpression of the glucose transporter GLUT-4, the subsequent enhancement of glucose uptake, and the anaerobic lactate generation. A late phenotype was characterized by the activation of P53/P21-mediated senescence. Notably, approximately 2% of AIF-/Y MEFs diminished both mitochondrial mass and ROS levels and spontaneously proliferated. These cycling AIF-/Y MEFs were resistant to caspase-independent cell death inducers. The AIF-deficient mouse strain was embryonic lethal between E11.5 and E13.5 with energy loss, proliferation arrest, and increased apoptotic levels. Contrary to AIF-/Y MEFs, the AIF KO embryos were unable to reprogram their metabolism toward anaerobic glycolysis. Heterozygous AIF+/- females displayed progressive bone marrow, thymus, and spleen cellular loss. In addition, approximately 10% of AIF+/- females developed perinatal hydrocephaly characterized by brain development impairment, meningeal fibrosis, and medullar hemorrhages; those mice died 5 weeks after birth. AIF+/- with hydrocephaly exhibited loss of ciliated epithelium in the ependymal layer. This phenotype was triggered by the ROS excess. Accordingly, it was possible to diminish the occurrence of hydrocephalus AIF+/- females by supplying dams and newborns with an antioxidant in drinking water. Conclusions: In a single knockout model and at 3 different levels (cell, embryo, and adult mice) we demonstrated that by controlling the mitochondrial OXPHOS/metabolism, AIF is a key factor regulating cell differentiation and fate. Additionally, by providing new insights into the pathological consequences of mitochondrial OXPHOS dysfunction, our new findings pave the way for novel pharmacological strategies.